Analysis of Monte-Carlo collision method with argon and helium background gases at different RF-powers and pressures in ELTRAP device - Ali, Hassan; Ali, Nisar; Metwally, Ahmed Sayed M.; Ali, Arshad; Jabeen, Musarrat (Ain Shams Engineering Journal, 2024)
The impact of confined excited electron with argon and helium background gases is systematically studied using Monte-Carlo particle-in-cell simulations for various low powers (1.0–8.0 V) and pressures (1.50 × 10−8 Torr and 3.75 × 10−9 Torr) in ELTRAP device. The results of these numerical studies showed that the heating effect of the excited confined electron plasma density of 5 × 1014 m−3 within the Brillouin limit (ne≤[Formula presented]=31.086×1019m-3) resulted a higher temperature (eV) and increased collision time in argon as a background gas as compared to helium gas. The axial temperature (eV) has a higher value than the radial temperature (eV) and increases with the increase in RF-Powers and pressures. The maximum kinetic energy of excited confined electrons occurred in the range of 0.03–0.04 m radially due to the maximum self-electric field intensity in simulation time up to 20 µs. The electric field decreases when the collision frequency is increased. The secondary electron production and ionization are higher than expected at a background pressure of 1.50 × 10−8 Torr as compared to 3.75 × 10−9 Torr. The remaining secondary electrons were always ejected from the symmetry axis of the device. It was observed that the production of secondary electrons is proportional to the ionization rate.
CRIS-Team Scopus Importer:2024-11-22
Keywords: Collision time; Heating effect; Monte-Carlo particle-in-cell simulations; Non-neutral plasma